2018
DOI: 10.3390/ma11101944
|View full text |Cite
|
Sign up to set email alerts
|

Low Cycle Fatigue Behavior of Steam Generator Tubes under Axial Loading

Abstract: Compared with the fatigue properties of the material (Inconel Alloy 690), the real fatigue lives of tubes are more meaningful in the fatigue design and assessment of steam generator (SG) tube bundles. However, it is almost impossible to get a satisfactory result by conducting fatigue tests on the tube directly. A tube with a uniform and thin wall easily fails near the clamping ends under cyclic loading due to the stress concentration. In this research, a set-up for fatigue tests of real tubes is proposed to ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In order to obtain the local stress-strain state around the notch, elastic analysis and elastoplastic analysis were carried out respectively. Meanwhile, the cyclic stress-strain relation of material for elastoplastic analysis is described by Ramberg-Osgood model [20]:…”
Section: Finite Element Modelmentioning
confidence: 99%
“…In order to obtain the local stress-strain state around the notch, elastic analysis and elastoplastic analysis were carried out respectively. Meanwhile, the cyclic stress-strain relation of material for elastoplastic analysis is described by Ramberg-Osgood model [20]:…”
Section: Finite Element Modelmentioning
confidence: 99%
“…The results show that the cyclic stress response of 2205 is primary cyclic hardening followed by long-term cyclic softening, while 316 L shows secondary hardening at larger strain amplitudes. Xing et al [ 12 ] investigated the fatigue properties of Inconel 690. The results of cyclic stress–strain response investigation showed that the response strongly depended on strain amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Non-monotonic alternation of stress states may lead to permanent changes in the structure of materials and is often the cause of the limited functionality of components. The vast majority of machines and engineering structures are subjected to complex and time-varying operational loads [1][2][3][4][5][6]. Generally, the loads can be dynamic, i.e., caused by forces and moments varying in time.…”
Section: Introductionmentioning
confidence: 99%